Innovation of Semarang City National Land Agency Office in preventing land rights dispute based on complaint service and e-certificate - Sri Rahayu, Fanny Agustina (Journal of Law Science, 2025)
Land certificates are issued as proof of ownership and the interests of rights holders who have registered with the National Land Office. It is hoped that the issuance of certificates as juridical data can minimise the occurrence of land certificate disputes, but in fact what happens in the field there are still land certificates in dispute, this usually occurs because of a sense of dissatisfaction that is subjective and there are parties who feel disadvantaged by other parties. This article aims to analyse the innovation of the Semarang City National Land Agency Office in preventing land certificate disputes using a normative juridical approach combined with empirical juridical. From the results of the research, it can be concluded that the innovations made by the Semarang City National Land Agency Office are providing complaint services and updating physical land certificates (analogue) to electronic land certificates (sertipikat-el), one of the reasons for this innovation is expected to reduce and prevent land certificate disputes in Semarang City. The Semarang City Land Office was ranked first in issuing the most electronic certificates for routine services in fiscal year 2024, indicating that the implementation of innovations has been effective and efficient